1996
DOI: 10.1099/00222615-44-2-135
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Fc  receptors on neutrophils and monocytes may reflect ongoing bacterial infection

Abstract: The FcyR receptors for IgG, FcyRI, FcyRII and FcyRIII were measured on neutrophils and monocytes from 36 patients suspected of systemic infection. These results were compared with 30 blood donor controls to assess the level of expression as an early indicator of bacterial infection. FcyRI expression on neutrophils was found to be significantly increased from patients with systemic or localised infections, when compared to the non-infected patient group, i.e., patients with no cultural evidence of bacterial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 14 publications
4
40
3
Order By: Relevance
“…During bacterial infection, the expression of CD64 on activated neutrophils was markedly increased (18,33,34). More important, it has also been shown that neutrophils of preterm infants expressed CD64 antigen to an extent similar to those of older children and adults (18).…”
Section: Diagnosis Of Neonatal Infection By Cd64mentioning
confidence: 85%
“…During bacterial infection, the expression of CD64 on activated neutrophils was markedly increased (18,33,34). More important, it has also been shown that neutrophils of preterm infants expressed CD64 antigen to an extent similar to those of older children and adults (18).…”
Section: Diagnosis Of Neonatal Infection By Cd64mentioning
confidence: 85%
“…Neutrophil CD64 expression is a useful biomarker for improving the diagnosis and management of hospital patients with bacterial infections [4,8]. Also, it can be incorporated as a valuable marker to exclude neonatal sepsis (NS) [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…61 During bacterial infections, however, the neutrophil expression of CD64 is markedly increased. [63][64][65] Studies have confirmed that the level of CD64 expression is significantly higher in patients with infectious SIRS as compared to patients with noninfectious SIRS as well as adults and children. 66,67 All the indexes in our group were within the normal range, although surgery is known to elevate the levels of CD64 expression on monocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 64%